A 3, 4-dihalo-2(5H)-furanone initiated ring-opening reaction of DABCO in the absence of a metal catalyst and additive and its application in a one-pot two-step reaction. Issue 14 (25th June 2019) - Wu, Han-Qing; Yang, Kai; Chen, Xiao-Yun; Arulkumar, Mani; Wang, Neng; Chen, Si-Hong; Wang, Zhao-Yang
Abstract : An environmental friendly protocol for metal/additive-free synthesis of potential bioactive compounds from 3, 4-dihalo-2(5 H )-furanone and DABCO is described. Abstract : In the absence of metal catalysis and an additive, with ethyl acetate as a solvent at 95 °C under air atmosphere for 2 h, an eco-friendly and practical protocol for the synthesis of 4-ethylpiperazine derivatives through a 3, 4-dihalo-2(5 H )-furanone initiated ring-opening reaction of DABCO is developed. Satisfactory reactivity with moderate to excellent yields and 100% atom economy are observed. This potential bioactive synthon promoted ring-opening reaction is not only important for the development of new drugs, but also suitable for other cyclic tertiary amines ( e.g. 1-methylpyrrolidine) with good yields. In addition, due to the newly generated alkyl halide structural unit in the product, its application in one-pot two-step reactions with different kinds of nucleophilic reagents can be achieved as designed.